Bodyshop the Photoshop retouching guide for the face and body - Nitzsche, Birgit; Rose, Karsten; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2010)
"This full-color book will show how both the newest and previous versions of Photoshop can be used to retouch and enhance the entire human form."--Resource description page.
Description based on print version record.
Includes index.
Keywords: Adobe Photoshop; Photography -- Retouching -- Handbooks, manuals, etc; Photography -- Digital techniques -- Handbooks, manuals, etc; Portrait photography -- Handbooks, manuals, etc; Computer graphics -- Computer programs; Electronic books